Institutional Trust, Ethical Governance, and Public Sector Performance in Timor-Leste - Novia Rosa de Sousa; Miswanto; Frasto Biyanto; Baldric Siregar (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Purpose: This study aims to analyze the influence of ethical governance and HRM practices on public sector performance, with institutional trust as a mediating variable, among public sector employees in Timor-Leste. Methods: This study employed a quantitative explanatory approach using purposive sampling, involving 150 respondents who work as civil servants across ministries and government agencies in Timor-Leste. Data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. Results: The results show that ethical governance and HRM practices have a positive and significant effect on institutional trust, while their direct effects on public sector performance are not significant. Institutional trust, in turn, has a positive and significant effect on public sector performance and fully mediates the relationship between both ethical governance and HRM practices toward performance. Implications: These findings suggest that public sector institutions in Timor-Leste should prioritize building institutional trust as a strategic mechanism to translate ethical governance and human resource practices into improved organizational performance, rather than relying on these practices alone.